Moderating Effects of Perceived Neighborhood Factors on Intimate Partner Violence, Psychological Distress, and Suicide Risk. Issue 21 (November 2021) - Fedina, Lisa; Mushonga, Dawnsha R.; Bessaha, Melissa L.; Jun, Hyun-Jin; Narita, Zui; DeVylder, Jordan
Neighborhood factors such as instability and weakened social ties have been linked to both intimate partner violence (IPV) and poor mental health outcomes; however, research has not yet investigated the relationship between IPV and gentrification-specific change, including whether gentrification-related neighborhood factors affect mental health symptoms commonly associated with IPV. This study aims to determine if (a) perceptions of neighborhood connectedness and recent compositional changes (e.g., residential mobility, crime, and infrastructure) are associated with IPV exposure and (b) perceived neighborhood connectedness and compositional change moderates the relationship between IPV and mental health symptoms (i.e., psychological distress, suicidal ideation, suicide attempts). Data from the 2017 Survey of Police-Public Encounters were used, which is an online, cross-sectional, general population survey administered to male and female adults residing in New York City and Baltimore ( N = 1, 000). Findings suggest that higher levels of neighborhood disconnectedness were associated with higher levels of IPV, whereas higher levels of neighborhood compositional change were associated with lower levels of IPV. Neighborhood disconnectedness and compositional change worsened psychological distress symptoms and suicide risk most strongly among individuals exposed to IPV. Violence prevention and intervention approaches should consider the extent to which neighborhood instability, related to community connectedness and recent compositional change, impacts the safety and mental health of victims of IPV.